Infrastructure and Spatial Transformation of Mrzla Vodica Village in Croatia - Morana Jarec (Etnoantropološki Problemi, 2024)
Infrastructure projects, encompassing the construction of roads, railways, power facilities, and other structures, have a tangible impact on the physical landscape. When implemented within or through a settlement, these projects also influence cultural and social aspects of life. Despite their intention to enhance citizens' well-being as part of modernization endeavours, infrastructure initiatives often produce uneven effects on different social groups. This study focuses on the transformative processes that unfolded in the village of Mrzla Vodica, located in Gorski Kotar, Croatia, following the construction of the Lujzijana Road in the early 19th century and a dam in the mid-20th century, and all the way to the present day. Employing a classic ethnographic approach and a literature review, this research aims to demonstrate how infrastructure can generate both prosperity and significant disruptions to space, potentially leading to the decline or even disappearance of a certain community. By shedding light on the inequality produced by infrastructural development, this study tries to contribute to a deeper understanding of the modernization processes in rural areas.